Fungsi Lembaga Legislatif Versus Kelompok Kepentingan di DPR RI: Kasus Penetapan Anggaran Pendapatan dan Belanja Negara - Haryati, Dedeh (Jurnal Bina Praja, 2009)
This research is to analyze how DPR-RI run the function of budgeting that is in the usage of budgeting rights, especially in stipulating of APBN. This research found the external factor drives a change in internal factor and politics that is the role of interest group influence in the usage of budgeting DPR-RI rights is specially in the course of stipulating APBN in the Committee Budgeting of DPR-RI.